Emerging trends and hot spots of NLRP3 inflammasome in neurological diseases: A bibliometric analysis - Yu, Xiaoyan; Yu, Chuan; He, Wenfang (Frontiers in Pharmacology, 2022)
Background: NLRP3 inflammasome has been of great interest in the field of neurological diseases. To visualize the research hotspots and evolutionary trends in this area, we collected the relevant articles in the Web of Science Core Collection database from 2010 to 2022 and analyzed them using CiteSpace software. Methods: We performed a systematic search of the literature within the Web of Science Core Collection database using the strategy described below: TS=NLRP3 inflammasome AND TS=neurological diseases OR TS=neurological disorder OR TS=brain disorder OR TS=brain injury OR TS=central nervous system disease OR TS=CNS disease OR TS=central nervous system disorder OR TS=CNS disorder AND Language = English from 2010 to 2022. The type of literature was limited to articles and reviews. The data were processed using CiteSpace software (version 5.8.R3). Results: A total of 1217 literature from 67 countries/regions and 337 research institutions was retrieved. Publications in this area have increased rapidly since 2013. China presents the highest number of published articles, but the United States has a higher centrality and h-index. The top five most published institutions and authors are from China, Zhejiang University and Li Y ranking first, respectively. Of the ten most cited articles, Prof. Heneka MT and colleagues accounted for three of them. In terms of the co-occurrence keyword diagram, the five most frequent keywords are “nlrp3 inflammasome”, “activation”, “oxidative stress”, “expression”, and “alzheimers disease”. Conclusion: The research of NLRP3 inflammasome in neurological disorders is overall developing well. Chinese scholars contributed the most significant number of articles, while researchers from developed countries presented more influential papers. The importance of NLRP3 inflammasome in neurological diseases is widely appreciated, and the mechanism is under study. Moreover, NLRP3 inflammasome is emerging as a promising therapeutic target in treating neurological disorders. However, despite decades of research, our understanding of NLRP3 inflammasome in central nervous system diseases is still lacking. More and more profound research is needed in the future.